1994
DOI: 10.1016/0928-8244(94)90104-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo human immune response to transferrin-binding protein 2 and other iron-regulated proteins of Neisseria meningitidis

Abstract: When grown under iron restriction, Neisseria meningitidis expresses new outer-membrane proteins, some of which are antigenic and potentially useful as vaccine components. This is particularly relevant to N. meningitidis serogroup B, against which neither polysaccharide nor conjugate vaccines are effective. We investigated recognition of N. meningitidis serogroup B outer-membrane antigens by three sera from patients recovered from meningitis. Recognition of antigens from the homologous strain provided informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The outer membrane proteins that have been reported to be recognized by the human immune response during infection are the PorA, PorB, Opc, and iron-regulated proteins (13,32). In human trials, current experimental vaccines based on PorA induce immunity that is subtype restricted (32) and may also be influenced by further intrasubtype variations (26).…”
Section: Discussionmentioning
confidence: 99%
“…The outer membrane proteins that have been reported to be recognized by the human immune response during infection are the PorA, PorB, Opc, and iron-regulated proteins (13,32). In human trials, current experimental vaccines based on PorA induce immunity that is subtype restricted (32) and may also be influenced by further intrasubtype variations (26).…”
Section: Discussionmentioning
confidence: 99%
“…that TbpB should be considered as a candidate for a possible vaccine against N. meningitidis infection (1)(2)(3)19). TbpB antibodies can be measured in convalescent-phase sera from patients with meningococcal disease (18,19,22); they are protective in a mouse model of infection, and they are also bactericidal in laboratory animals (24). However, TbpB is highly variable in different strains of N. gonorrhoeae and, taken together with lower tbpB transcript amounts produced in subject samples, may explain why we observed lower titers of IgG antibody against TbpB antigen than against TbpA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that antibodies to meningococcal Tbp complexes and to isolated proteins have been detected in both patients and carriers and that these antibodies were able to cross-react with TbpA or TbpB isolated from different meningococci (3,11,16,19). However, in all cases, these conclusions were based on Western blot analysis or enzyme-linked immunosorbent assay (ELISA) performed on purified Tbp complexes.…”
Section: Discussionmentioning
confidence: 77%